Moving Beyond Intelligence: Predicting Academic Behaviors and Official GPA in Undergraduate Students with Implicit Theories - Carey Dowling; C. Veronica Smith; Yue Yin; Jeffrey M. Williams (Journal of the Scholarship of Teaching and Learning)
People view attributes, including intelligence, through implicit theories, or mindsets, whereby they are seen as unchangeable (entity mindset) or malleable (incremental mindset) (Dweck & Leggett, 1988). Previous research examining implicit theories of intelligence in undergraduate students has found mixed results for their ability to predict academic achievement (Sisk et al., 2018). The present studies examined the Academic Beliefs Scale (ABS), a new measure designed to measure implicit theories of academic success in undergraduate students, and its relationship to academic achievement in undergraduate students. In Study 1, the relationships between undergraduate students’ implicit theories of academic success, as measured by the ABS, but not the incremental theory of intelligence, as measured by the Theories of Intelligence Scale (TIS, Dweck, 1999), and official GPA were statistically mediated by poor study habits, procrastination, and self-handicapping. In Studies 2A and 2B, the psychometric properties of the ABS were found to be satisfactory. Furthermore, the correlations between the entity (negative) and incremental (positive) theories of academic success and GPA were statistically mediated by good academic habits. Future research with undergraduates should continue to examine the merits of the ABS psychometrically and as a predictor of additional academic outcomes in addition to, or in place of, the TIS.